1962
DOI: 10.1152/jappl.1962.17.4.689
|View full text |Cite
|
Sign up to set email alerts
|

Human auditory system response to modulated electromagnetic energy

Abstract: The intent of this paper is to bring a new phenomenon to the attention of physiologists. Using extremely low average power densities of electromagnetic energy, the perception of sounds was induced in normal and deaf humans. The effect was induced several hundred feet from the antenna the instant the transmitter was turned on, and is a function of carrier frequency and modulation. Attempts were made to match the sounds induced by electromagnetic energy and acoustic energy. The closest match occurred when the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
1

Year Published

1974
1974
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(80 citation statements)
references
References 0 publications
1
76
1
1
Order By: Relevance
“…Frey (136,137) has reported that individuals can detect pulse-modulated electromagnetic energy at wavelengths of cm and at average power densities of 0.4 to 2.1 mW/cm2. The reported sensations were usually of an auditory nature and described as hissing, buzzing, or clicking sounds.…”
Section: Neural Effectsmentioning
confidence: 99%
“…Frey (136,137) has reported that individuals can detect pulse-modulated electromagnetic energy at wavelengths of cm and at average power densities of 0.4 to 2.1 mW/cm2. The reported sensations were usually of an auditory nature and described as hissing, buzzing, or clicking sounds.…”
Section: Neural Effectsmentioning
confidence: 99%
“…Guy et al [1975] and Lin et al [1978Lin et al [ , 1979 showed that electrophysiological responses of the auditory pathway in cats to RF pulses is similar to the response to acoustic stimuli and, by studying the responses after lesions were made in successive parts of the auditory pathway, confirmed that the primary site of transduction of the RF energy was outside or at the cochlea. The detection of electric potentials in auditory neurons in response to RF exposure was expected based on the results of studies that demonstrated subjective auditory perception [Frey, 1962] and cochlear microphonics . Seaman [1990] described a model for thresholds of auditory neurons to RF pulses that was consistent with thresholds measured in the cat for 20-200 ms pulses.…”
Section: Similarity Of Auditory Response To Rf Energy and Conventionamentioning
confidence: 99%
“…The apparent location of the sound, which was described as a short distance behind the head, was the same regardless of the body's orientation to the radar [Frey, 1961]. In later reports [Frey, 1962[Frey, , 1963, RF hearing was described as a ''buzz, clicking, hiss, or knocking'' sound. Table 1 contains descriptions of these and other sounds reported by human beings exposed to pulsed RF fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been studied as a receiver and a source for sound and electromagnetic waves 1,2,3,4 . We suggest using pulse diagnostics in order to take into account the physiological background of auditory system functioning.…”
Section: Introductionmentioning
confidence: 99%